1980
DOI: 10.1111/j.1476-5381.1980.tb09775.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adrenalectomy and Hypophysectomy on Enkephalin Content of the Rat Hypothalamus

Abstract: 1Hypothalamic content of enkephalin in rats has been measured by bioassay against methionineenkephalin on field-stimulated mouse vas deferens after acid extraction and purification using Amberlite XAD-2 resin. 2 Surgical stress lowered hypothalamic enkephalin content initially but 6 days after operation the content was higher in sham-operated than in adrenalectomized animals. 3 Corticosteroid replacement therapy showed that hypothalamic enkephalin content was not related directly to circulating corticosteroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Thus Leu-enkephalin seemed to reinforce the negative feedback mechanisms within the HPA system which are activated by stress (Jones, Hillhouse & Burden, 1976), and produced an effect which opposed that of Met-enkephalin. (Rossier, Guillemin & Bloom, 1978;Gibson, Ginsburg, Hart & Kitchen, 1980). The present results would suggest that activation of Met-enkephalin containing nerves and Leuenkephalin containing nerves would produce opposing effects on the HPA system and therefore that the degree of activation of the system by stress may be dependent upon the balance of activity within the brain of the endogenous opioid peptides.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Thus Leu-enkephalin seemed to reinforce the negative feedback mechanisms within the HPA system which are activated by stress (Jones, Hillhouse & Burden, 1976), and produced an effect which opposed that of Met-enkephalin. (Rossier, Guillemin & Bloom, 1978;Gibson, Ginsburg, Hart & Kitchen, 1980). The present results would suggest that activation of Met-enkephalin containing nerves and Leuenkephalin containing nerves would produce opposing effects on the HPA system and therefore that the degree of activation of the system by stress may be dependent upon the balance of activity within the brain of the endogenous opioid peptides.…”
mentioning
confidence: 63%
“…It is of interest that Buckingham & Hodges (1979) have recently found that endogenous opioid peptides can produce mutually antagonistic effects on the output of corticotrophin releasing hormone in vitro, and Larssen, Childers & Snyder (1979) have identified distinct Met-enkephalin containing and Leu-enkephalin containing nerve tracts in brain. It is known that various types of stress cause a reduction in hypothalamic enkephalin content, and this has been interpreted as being a result of stress-induced activation of central enkephalin containing nerves (Rossier, Guillemin & Bloom, 1978;Gibson, Ginsburg, Hart & Kitchen, 1980). The present results would suggest that activation of Met-enkephalin containing nerves and Leuenkephalin containing nerves would produce opposing effects on the HPA system and therefore that the degree of activation of the system by stress may be dependent upon the balance of activity within the brain of the endogenous opioid peptides.…”
Section: Resultsmentioning
confidence: 99%
“…In particular there is evidence that stress responses are modulated by opioids. For example footshock alters levels of plasma P-endorphin and hypothalamic [Leu] enkephalin (Rossier et al, 1977;1978) and adrenalectomy lowers the content of hypothalamic opioid peptides (Gibson et al, 1980). In addition the basal and stress-induced secretion of 'Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…While the status of the enkephalin or endorphin release in the brain of hypophysectomized animals is unknown, the steady state brain levels of these peptides have been shown in some studies to remain unchanged in such animals (Rossier et al, 1977;Kobayashi etal., 1978;Gibson, Ginsburg, Hart & Kitchen, 1980). The ability of (-)-Nal to reverse the action of the exogenously administered opioid agonists was not affected ir these animals.…”
Section: Disussionmentioning
confidence: 89%
“…The decreased effect of Nal might be due to a weak enkephalin-mediated inhibition of cholinergic neurones resulting from a diminished release of endogenous opioids. While the status of the enkephalin or endorphin release in the brain of hypophysectomized animals is unknown, the steady state brain levels of these peptides have been shown in some studies to remain unchanged in such animals (Rossier et al, 1977;Kobayashi etal., 1978;Gibson, Ginsburg, Hart & Kitchen, 1980). However, in a recent study it was shown that removal of the anterior lobe of rat pituitary lowers P-endorphin levels in the hypothalamus and in the periventricular tissue (Przewlocki, Millan, Gramsch, Milan & Herz, 1982).…”
Section: Disussionmentioning
confidence: 99%